Geographic variations in the PARADIGM-HF heart failure trial - Kristensen, Søren Lund; Martinez, Felipe; Jhund, Pardeep S; Arango, Juan Luis; Bĕlohlávek, Jan; Boytsov, Sergey; Cabrera, Walter; Gomez, Efrain; Hagège, Albert A; Huang, Jun; Kiatchoosakun, Songsak; Kim, Kee-Sik; et al. (European heart journal, 2016)
AIMS: The globalization of clinical trials has highlighted geographic variations in patient characteristics, event rates, and treatment effects. We investigated these further in PARADIGM-HF, the largest and most globally representative trial in heart failure (HF) to date. METHODS AND RESULTS: We looked at five regions: North America (NA) 602 (8%), Western Europe (WE) 1680 (20%), Central/Eastern Europe/Russia (CEER) 2762 (33%), Latin America (LA) 1433 (17%), and Asia-Pacific (AP) 1487 (18%). Notable differences included: WE patients (mean age 68 years) and NA (65 years) were older than AP (58 years) and LA (63 years) and had more coronary disease; NA and CEER patients had the worst signs, symptoms, and functional status. North American patients were the most likely to have a defibrillating-device (54 vs. 2% AP) and least likely prescribed a mineralocorticoid receptor antagonist (36 vs. 65% LA). Other evidence-based therapies were used most frequently in NA and WE. Rates of the primary composite outcome of cardiovascular (CV) death or HF hospitalization (per 100 patient-years) varied among regions: NA 13.6 (95% CI 11.7-15.7) WE 9.6 (8.6-10.6), CEER 12.3 (11.4-13.2), LA 11.2 (10.0-12.5), and AP 12.5 (11.3-13.8). After adjustment for prognostic variables, relative to NA, the risk of CV death was higher in LA and AP and the risk of HF hospitalization lower in WE. The benefit of sacubitril/valsartan was consistent across regions. CONCLUSION: There were many regional differences in PARADIGM-HF, including in age, symptoms, comorbidity, background therapy, and event-rates, although these did not modify the benefit of sacubitril/valsartan. CLINICAL TRIAL REGISTRATION URL: http://www.clinicaltrials.gov. Unique identifier: NCT01035255.
Keywords: Heart Failure; hospitalizace; Asie; lidé středního věku; lidé; srdeční selhání; senioři; Asia; Evropa; Europe; Aged; Middle Aged; Hospitalization; Humans